Valorizzare il patrimonio storico-artistico creando occupazione sociale - MediaGEO, redazione (Archeomatica, 2013)
This year the Accenture Italian Foundation has organized the competition "ARS - Art that creates social employment", an opportunity to promote initiatives aimed at enhancing the historical and artistic heritage Italian harnessing the creativity and technology made in Italy, in order to create more job opportunities. The call opened to companies, associations and institutions, has offered a million of Euros to the best idea for the valorization of the cultural heritage.